2015
DOI: 10.1088/1758-5090/7/4/044104
|View full text |Cite
|
Sign up to set email alerts
|

3D bioprinting of BMSC-laden methacrylamide gelatin scaffolds with CBD-BMP2-collagen microfibers

Abstract: Three-dimensional (3D) bioprinting combines biomaterials, cells and functional components into complex living tissues. Herein, we assembled function-control modules into cell-laden scaffolds using 3D bioprinting. A customized 3D printer was able to tune the microstructure of printed bone mesenchymal stem cell (BMSC)-laden methacrylamide gelatin scaffolds at the micrometer scale. For example, the pore size was adjusted to 282 ± 32 μm and 363 ± 60 μm. To match the requirements of the printing nozzle, collagen mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
105
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(105 citation statements)
references
References 60 publications
(70 reference statements)
0
105
0
Order By: Relevance
“…Currently, there are numerous studies that focus on 3D bioprinting of cells and scaffold materials together to create 3D artificial constructs for organ transplantation and drug screening [15,16]. 3D bioprinting is not only useful for 3D cell interaction studies, but also it potentially helps in regeneration therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are numerous studies that focus on 3D bioprinting of cells and scaffold materials together to create 3D artificial constructs for organ transplantation and drug screening [15,16]. 3D bioprinting is not only useful for 3D cell interaction studies, but also it potentially helps in regeneration therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting self-standing structures could then be permanently solidified via UV-initiated crosslinking (Fig. 7a) [136, 137]. Multi-layered microfibrous structures of GelMA hydrogels could be fabricated using this bioprinting system (Fig.…”
Section: Spatial Control Of Hydrogelsmentioning
confidence: 99%
“…(i) Viability and spreading of fibroblasts encapsulated in the bioprinted construct at Day 5. Reproduced with permission from: (a–e) [136, 137] (f–i) [138]. …”
Section: Figurementioning
confidence: 99%
“…To achieve this, the bioink materials can be modified/ functionalized with ECM components. In a recent study, collagen films were first grinded using a crushingparticle desk crusher and passed through a 38μm mesh to get collagen microfibers of length 22 ± 13μm [111] . These collagen microfibers were linked with bone morphogenetic protein-2 (BMP2) that contained collagen-binding domain (CBD-BMP2).…”
Section: Emerging Strategies In Bioprintingmentioning
confidence: 99%
“…The CBD-BMP2 was printed onto bone marrow mesenchymal stem cells-laden methacrylamide gels. It was reported that these bone marrow mesenchymal stem cells differentiated into osteocyte cells due to the presence of ECM components such as collagen and BMP-2 in CBD-BMP2 [111] . Cells are subjected to a mild stress (thermal or mechanical) during bioprinting that may affect the cell viability in the printed constructs.…”
Section: Emerging Strategies In Bioprintingmentioning
confidence: 99%